AB0113 ARTHRITIS IS ASSOCIATED WITH CEREBROVASCULAR ENDOTHELIAL DYSFUNCTION: MECHANISTIC INSIGHTS IN THE RAT ADJUVANT-INDUCED ARTHRITIS MODEL. (June 2019) - Bordy, Romain; Totoson, Perle; Bouressam, Marie-Lynda; Dupuis, François; Verhoeven, Frank; Wendling, Daniel; Demougeot, Céline
Abstract : Background: Stroke is the second cause of premature mortality and sudden death in rheumatoid arthritis (RA) after myocardial infarction 1 . The mechanisms involved in the high risk of stroke are currently unknown, but data from the general population argue for a contribution of cerebrovascular dysfunction. Objectives: The aim of our study was to investigate cerebrovascular function in the rat adjuvant-induced arthritis (AIA) model and to unravel the mechanisms involved, with special emphasis on the pathways regulating nitric oxide (NO) vascular availability. Methods: Arthritis was induced in 6 weeks-old male Lewis rats by a single injection at the base of the tail of a suspension of Mycobacterium butyricum in Freund's incomplete adjuvant. A control group received saline. Thirty-three days after induction, middle cerebral artery (MCA) were dissected and mounted on two glass micropipettes in a small vessel arteriograph before being pressurized at 80 mmHg. Endothelial function was evaluated in vessels pre-contracted with serotonin (10 -6 M) by measuring the relaxant effect of bradykinin (BK, 10 -6 M), adenosine diphosphate (ADP, 10 -6 M) and cumulative concentrations of acetylcholine (Ach, 10 -12 to 10 -4 M) in the presence or not of a Nitric Oxide Synthase (NOS) inhibitor (L-NAME, 10 -4 M), an arginase inhibitor (nor-NOHA, 10 -4 M), a NOS co-factor (BH4, 10 -7 M), an analog of superoxide dismutase (Tempol, 10 -4 M). The relaxant response of vascular smooth muscle cells to a NO-donor (SNP, 10 -12 to 10 -4 M) was also evaluated. Results: Vasodilation induced by BK, ADP and Ach were significantly reduced in AIA compared to controls rats (p<0.0001). L-NAME decreased Ach-induced relaxation in controls but not in AIA rats. By contrast, nor-NOHA (p<0.0001), Tempol (p<0.0001) and BH4 (p<0.02) significantly improved Ach-induced relaxation in AIA but not in controls. The response to SNP was not different between the 2 groups. Conclusion: Arthritis is associated with endothelial dysfunction in MCA. These results indicate that this model is relevant for mimicking the cerebrovascular impairments recently observed in RA patients 2 . Cerebrovascular endothelial dysfunction relies on a low NOS activity, a high arginase activity and excessive superoxide anions production. Overall data suggest that therapies able to reverse the imbalance in NOS/arginase pathways would be efficient for reducing the incidence of cerebrovascular events in RA. References: [1] Avina-Zubieta, J. A., Thomas, J., Sadatsafavi, M., Lehman, A. J. & Lacaille, D. Risk of incident cardiovascular events in patients with rheumatoid arthritis: a meta-analysis of observational studies. Ann. Rheum. Dis. 71, 1524–1529 (2012). [2] Oláh C, Kardos Z, Sepsi M, Sas A, Kostyál L, Bhattoa HP, Hodosi K, Kerekes G, Tamási L, Valikovics A, Bereczki D, Szekanecz Z. Assessment of intracranial vessels in association with carotid atherosclerosis and brain vascular lesions in rheumatoid arthritis. Arthritis Res Ther. 19(1):213 (2017). Disclosure of Interests: None declared